Penatalaksanaan Depigmentasi Gingiva Fisiologis dengan Teknik Sederhana (Laporan Kasus) - Hanifah Salma Rosa; Howis Josephine; Ira Wijayanti; Ricky Anggara Putranto (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Pigmentation of gingiva is a condition where the color of gingiva is purple, brown, or black instead of coral pink. Gingival pigmentation is caused by melanin pigment and occurs through three stages, namely melanocyte activation, melanin synthesis, and melanin expression. Gingival pigmentation can affect the aesthetic appearance of a smile. Thus, several depigmentation techniques are used to overcome this problem using a scalpel, laser, bur, cryosurgery, electrosurgery, and radiosurgery with respective pros and cons. Case: A 44-year-old woman complains regarding her upper front gum discoloration with a physiological gingival pigmentation. Result diagnosis: A case is reported herein, which conventional ablation depigmentation technique using bur. Conclusion: The method used in this case is recommended due to the easy, simple, and safe procedure, low cost, and less working time than the other techniques.